Analysis of Potassium, Magnesium and Sodium Contents in Chayote (Sechium edule Sw.) from Sedoa, North Lore District, Poso - Lage, Mersed Djein; Ningsih, Purnama; Sakung, Jamaluddin (Jurnal Akademika Kimia, 2019)
Chayote has minerals such as potassium, magnesium and sodium which are very beneficial for the human body. This study aimed to determine potassium (K), magnesium (Mg) and sodium (Na) in ripe and young chayote extracts as well as old and young chayote seeds extracts by using quantitative analysis method with atomic absorption spectrophotometry. Potassium, magnesium and sodium were analysed at a wavelength of 766.5 nm, 285.2 nm and 589 nm. The results showed that the potassium contents are 80.059 mg/100g in ripe chayote; 45.431 mg/100g in young chayote; 65.287 mg/100g in old chayote seed; and 73.014 mg/100g in young chayote seed. Sodium contents are 61.032 mg/100g in ripe chayote; 49.936 mg/100g in young chayote; 61.101 mg/100g in old chayote seed; and 71.621 mg/100g in young chayote seed. Additionally, magnesium contents are 47.327 mg/100g in ripe chayote; 74.324 mg/100g in young chayote; 57.658 mg/100g in old chayote seed; and 58.529 mg/100g in young chayote seed.